High-Throughput Genetic Screening of 51 Pediatric Cataract Genes Identifies Causative Mutations in Inherited Pediatric Cataract in South Eastern Australia. Issue 10 (1st October 2017) - Javadiyan, Shari; Craig, Jamie E; Souzeau, Emmanuelle; Sharma, Shiwani; Lower, Karen M; Mackey, David A; Staffieri, Sandra E; Elder, James E; Taranath, Deepa; Straga, Tania; Black, Joanna; Pater, John; et al.
Abstract: Pediatric cataract is a leading cause of childhood blindness. This study aimed to determine the genetic cause of pediatric cataract in Australian families by screening known disease-associated genes using massively parallel sequencing technology. We sequenced 51 previously reported pediatric cataract genes in 33 affected individuals with a family history (cases with previously known or published mutations were excluded) using the Ion Torrent Personal Genome Machine. Variants were prioritized for validation if they were predicted to alter the protein sequence and were absent or rare with minor allele frequency <1% in public databases. Confirmed mutations were assessed for segregation with the phenotype in all available family members. All identified novel or previously reported cataract-causing mutations were screened in 326 unrelated Australian controls. We detected 11 novel mutations in GJA3, GJA8, CRYAA, CRYBB2, CRYGS, CRYGA, GCNT2, CRYGA, and MIP ; and three previously reported cataract-causing mutations in GJA8, CRYAA, and CRYBB2 . The most commonly mutated genes were those coding for gap junctions and crystallin proteins. Including previous reports of pediatric cataract-associated mutations in our Australian cohort, known genes account for >60% of familial pediatric cataract in Australia, indicating that still more causative genes remain to be identified.